Methionine supplementation: potential for improving alveolar macrophage function through reverse cholesterol transport?. Issue 5 (5th May 2022) - O'Callaghan, Marissa; Helly, Feargal; Tarling, Elizabeth; Keane, Michael P.; McCarthy, Cormac
We read with great interest the article "Methionine supplementation for multi-organ dysfunction in MetRS-related pulmonary alveolar proteinosis" by Hadchouel et al [1]. The MARS1 (methionine tRNA synthetase) gene encodes the cytosolic methionine tRNA synthetase (MetRS), which plays a critical role in protein biosynthesis by charging tRNAs with methionine, leading to the formation of methionyl-tRNA. Pulmonary alveolar proteinosis (PAP) associated with a mutation in this gene causes severe disease and carries a high mortality rate. The authors found that methionine supplementation led to an improvement in respiratory status with clearance of extracellular lipoproteinaceous material, and normalisation of reactive oxygen species (ROS) production by peripheral blood monocytes. The authors hypothesised that this shift in ROS production following methionine treatment reflects resolution of macrophage dysfunction caused by the MARS1 mutation [1], and thus clinical improvement. While ROS plays an important and versatile role in macrophage mediated immunity, we believe this may be only one of the functional improvements in alveolar macrophages as a result of methionine therapy. We commend the authors on presenting these interesting findings and propose that methionine may also play a pivotal role in alveolar macrophage lipid catabolism and reverse cholesterol transport, thus affecting global macrophage function. Methionine may directly influence alveolar macrophage function through direct effect on reverse cholesterol transport https://bit.ly/2ZJlomg